2013
DOI: 10.1007/s10856-013-4853-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation of four magnesium–zinc–strontium alloys and their cytocompatibility with human embryonic stem cells

Abstract: Magnesium alloys have attracted great interest for medical applications due to their unique biodegradable capability and desirable mechanical properties. When designed for medical applications, these alloys must have suitable degradation properties, i.e., their degradation rate should not exceed the rate at which the degradation products can be excreted from the body. Cellular responses and tissue integration around the Mg-based implants are critical for clinical success. Four magnesium-zinc-strontium (ZSr41) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
73
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 52 publications
5
73
0
Order By: Relevance
“…An increasing β-phase volume fraction with increasing Sr content was observed for the ZSr41A-D alloys and is consistent with previous reports in literature [27]. In this systematic study, the samples were polished up to 0.25 μm polycrystalline diamond paste to show the morphology of the secondary phases in detail.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An increasing β-phase volume fraction with increasing Sr content was observed for the ZSr41A-D alloys and is consistent with previous reports in literature [27]. In this systematic study, the samples were polished up to 0.25 μm polycrystalline diamond paste to show the morphology of the secondary phases in detail.…”
Section: Discussionsupporting
confidence: 90%
“…Details pertaining to the metallurgical process and heat treatment used for alloy preparation are described elsewhere [26,27]. The heat-treated 1.0 mm thick sheets of ZSr41 alloys were cut into 5 × 5 mm squares.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we combine the well-known osteogenic properties of strontium with magnesium to generate a bioabsorbable implant material with stable Sr release after implantation, while tailoring the alloy's biocompatibility and degradation performance. Our previous research showed that addition of Sr in ternary Mg alloys improved the mechanical and corrosion properties [24,26], and addition of 1 wt.% Sr resulted in improved cytocompatibility with human embryonic stem cells when compared with 0.15, 0.5, and 1.5 wt.% Sr [25,26]. Therefore, the Mg-1Sr alloy (wt.%; designated in this study as J1 alloy per ASTM B275 standard [27] was chosen for the present in vivo study due to its suitable degradable, cytocompatible and mechanical properties [24,26].…”
mentioning
confidence: 99%
“…Our previous research showed that addition of Sr in ternary Mg alloys improved the mechanical and corrosion properties [24,26], and addition of 1 wt.% Sr resulted in improved cytocompatibility with human embryonic stem cells when compared with 0.15, 0.5, and 1.5 wt.% Sr [25,26]. Therefore, the Mg-1Sr alloy (wt.%; designated in this study as J1 alloy per ASTM B275 standard [27] was chosen for the present in vivo study due to its suitable degradable, cytocompatible and mechanical properties [24,26]. Furthermore, a solution and aging treatment was investigated to optimize the microstructure and degradation properties of the J1 alloy by tailoring the microstructure and distribution of second phases as shown extensively for other Mg alloys [13,28].…”
mentioning
confidence: 99%
“…Prevalently, Mg and coating strategies were tested concerning their degradation rate in vitro. Few studies addressed the biological outcome by extraction testing or exposing cells to the material for a short culture period only [31][32][33][34]. We wanted to examine the in vitro performance of the n-HA coating in a biological milieu as well as to reconsider if a direct in vitro test set up is suitable for evaluating highly degradable materials in extended culture times.…”
mentioning
confidence: 99%